2018
DOI: 10.1177/1059601118793750
|View full text |Cite
|
Sign up to set email alerts
|

Within- and Between-Team Coordination via Transactive Memory Systems and Boundary Spanning

Abstract: In this article, we suggest that the transactive memory system (TMS) and boundary-spanning literatures are useful for understanding how individuals in team-based collectives can be structured to improve within-and between-team coordination. We argue that such coordination can be facilitated-or thwarted-by boundary-spanning behaviors and patterns of knowledge exchange within and between teams. Our theorizing explains how an existing team TMS can offset the within-team coordination burdens typically associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…However, because MTM often takes employee focus away from the focal team (Mortensen, 2014) and the potential overall benefits of MTM may not be visible in any given team (Mortensen & Haas, 2018), leaders may be discouraged from actively supporting MTM (Martinsuo & Lehtonen, 2009). Thus, leaders must be able to recognize when the organizational context will allow for the potential benefits from MTM to be accrued, must possess the opportunity to schedule employees in ways that support a generative flow of information, and must hold the drive to actively support this structure (e.g., Crawford et al, 2019; Gupta & Woolley, 2018; Olabisi & Lewis, 2018; Reus et al, 2014).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because MTM often takes employee focus away from the focal team (Mortensen, 2014) and the potential overall benefits of MTM may not be visible in any given team (Mortensen & Haas, 2018), leaders may be discouraged from actively supporting MTM (Martinsuo & Lehtonen, 2009). Thus, leaders must be able to recognize when the organizational context will allow for the potential benefits from MTM to be accrued, must possess the opportunity to schedule employees in ways that support a generative flow of information, and must hold the drive to actively support this structure (e.g., Crawford et al, 2019; Gupta & Woolley, 2018; Olabisi & Lewis, 2018; Reus et al, 2014).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Furthering this perspective, Mortensen (2014) demonstrated that the percentage of time dedicated to the focal team increased team performance through decreasing membership model divergence and increasing transactive memory. Furthermore, Olabisi and Lewis (2018) concluded that there is a vicious cycle weakening team transactive memory system and consequently coordination within and across teams when the knowledge base and position of the boundary spanner are not properly managed. Thus, despite MTM potentially encouraging the diffusion of best practices and learning (Furukawa, 2016; Martinsuo, 2013), some of the challenges of competing for these resources (Cooper, Edgett, & Kleinschmidt, 1998; Dye & Pennypacker, 1999) and the benefits that can be attained when attention is dedicated to the focal team (Cummings & Haas, 2012; Maynard et al, 2012; Mortensen, 2014; Peng et al, 2013) may lessen the likelihood of MTM being embraced.…”
Section: Outcomes Of Mtmmentioning
confidence: 99%
See 1 more Smart Citation
“…These team members are called “boundary spanners”. Extrapolating from prior literature, she also explored where the optimal locations for those boundary spanners in the within‐ and between‐team communication networks might lie (Olabisi and Lewis, ).…”
Section: Implications For Practice and Theorymentioning
confidence: 99%
“…Specifically, team members have their various areas of specialized knowledge and skills, and they understand the knowledge map of the group and confidently rely on one another, which in turn facilitates them to work effectively and in a coordinated manner. By integrating members’ different knowledge structures, TMS enables teams and organizations to optimally allocate tasks and maximize the utilization of everyone’s expertise [27]. A number of researches have shown that TMS can lead to better team performance [28,29,30] as well as personal capabilities [14].…”
Section: Theoretical Backgroundmentioning
confidence: 99%